GAMBARAN DAN UPAYA PENINGKATAN WORK READINESS PADA INDIVIDU DEWASA AWAL YANG BELUM MENDAPATKAN PEKERJAAN - Feneta Fidi Kirani; Putu Regina Sanjiwani Prakasa; Farah Fauziah Vivany; Gardarias Aulia Arsi; Hafida Dewi Humairo (Universitas Mataram, 2022)
Work readiness is the possession of skills, knowledge, attitudes and understanding that will inspire fresh graduates to effectively complete assignments or work well. Individuals who have work readiness will find it easier to get a job. In general, fresh graduates are in the developmental stage of early adulthood, where their developmental task is to work. The purpose of this study is to provide benefits and efforts to increase work readiness in early adult individuals who have not yet found work. The type of research used is basic qualitative research and uses purposive sampling technique in the data collection process. Data analysis uses thematic analysis and credibility strengthening techniques using source triangulation and member checking. Based on the results of the analysis of research data shows that the skills, knowledge and attitudes related to job readiness in individuals are different. Early adult individuals generally show readiness in terms of perceptions of characteristics related to work situations as well as social abilities, adaptability and social interaction in work situations. In this study, there are several similarities between participants, namely having personal competencies (skills, knowledge, attitudes) and social relations that can shape their readiness to work. However, there are also some differences in terms of organizational knowledge, work attitudes, protocols, practices in the work environment, and work-related competencies. Things that can be done to increase work readiness or work readiness by fresh graduates are by honing and developing their abilities so that they can have work readiness by participating in career guidance programs, job training, internship programs, and other activities to improve work readiness.